A Survey Report on the Trust of Speakers Towards their First Language (Mother Language, 2025)
The text discusses a study that aims to explore trust among individuals who use their first language in a multilingual setting. The study seeks to understand the level of trust that speakers have in their first language within specific domains and applications. Through a survey-based approach, participants were asked to respond to statements related to various domains where the trust in their first language was examined. The findings revealed that participants generally expressed a high level of trust in their first language, particularly in domains such as their place of residence, the perceived usefulness of the first language, the learning necessity of the first language, confidence-building through its use, its simplicity, and its importance among the younger generation. Conversely, domains such as academic discussions, linguistic inferiority, social media posts, and multimedia choice elicited contrasting responses. Additionally, the research aims to examine the connection between trust in the first language and the speaker’s second language. The objective is to gain a deeper understanding of how speakers place their trust in their first language, which represents their mother tongue.Mother Language, 2024; 8(1-2): 70-100